Respuesta :

you can solve this by substitution.
First, find y.
x + y =7
-x on both sides

y = x -7
now substitute in second equation.
3x - (x-7) = 1
           +7 on both sides
3x - x = 8
2x = 8
x = 4
now that you know x = 4,
substitute it into the first equation
y + (4) = 7
y = 3

x =4 y =3 
For this system of equations, you can easily use the elimination method because y cancels eachother out. Look below for work \. 

x + y = 7                    2 + y = 7                              3(2) - y = 1
3x - y = 1                       y = 5                                  6 - y = 1
                                                                                      -y = -5
4x = 8                                                                          y = 5

x = 2

Final Answer: 
x=2, y=5 OR (2, 5) 

Hope this helps!! :)